A Rare Case of Recurrent Mucoepidermoid Carcinoma of the Nasal Vestibule. (13th September 2017) - Bedeković, Vladimir; Leventić, Miro; Jelavić, Boris; Trotić, Robert; Ries, Mihael; Kostić, Mirjana; Lauc, Tomislav
Abstract : We report a rare case of a large recurrent mucoepidermoid carcinoma (RMEC) in an 81-year-old female smoker, which has originated in the right nasal vestibule. The recurrent tumour was inadequately treated for 6 years. It was a slow-growing tumour for 3 years and then began to enlarge at a higher pace. In the next three years it has covered a large part of the face. The patient had refused any medical treatment. The tumour caused breathing and swallowing difficulties. Because of the profuse bleeding from the tumour, the patient underwent emergency surgery. Surgical treatment consisted of rhinectomy and resection of the central upper lip and part of the right cheek. The facial defect was reconstructed immediately. Recovery from surgery was fast with no complications. Postoperative Multislice Computed Tomography scan showed no metastases so the patient did not receive any chemotherapy or radiotherapy. During a 2.5 years' follow-up period there was no recurrence of the disease.